Chronic Dietary Exposures of 2,4-D Alter Pulmonary Expression of MYC-N - Geetika, Geetika (Indian Journal of Veterinary Anatomy, 2019)
The present study conducted in mice presented that high and low doses of 2,4-D exposure alone or in combination with LPS showed strong immunopositive activity for MYCN in airways epithelial and septal cells. The indirect ELISA data revealed that 2,4-D with or without LPS did not caused significant increase in the protein concentration of MYCN in BAL fluid. Data taken together suggesting that following exposure to 2,4-D alone or in combination with LPS, increases the pulmonary expression of MYCN without altering the expression in BAL fluid.